Words and deeds. Corporate Social Responsibility in higher education institutions - Rotengruber, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2019)
The purpose of the paper is twofold. Firstly, to formulate a definition of University social responsibility (which takes into account social expectations towards this institution and its internal determinants as well). The final result of this research is the definition built on two concepts. On one hand, it is a stakeholder policy, on the other hand, a whistleblower policy. These are the criteria of responsibility, that is to say, rules which make the institution transparent and open to social criticism. Secondly, the article tends to establish whether a university in Poland (treated as a dominant institution of knowledge) is rightly seen as an irresponsible partner of civil society. Form the business ethics perspective the university is the more responsible, the more intensive are its relations with the social environment represented by stakeholders and whistleblowers. When they do not play their parts properly, the relations must be considered dysfunctional. Additional explanation of this problem is provided by the theory of management. In a use of the concept of the final customer, public opinion can find out if it—really—is the main interlocutor of the university. Social partners of this institution focus their attention on politicians and public administration taken as the alternative final customer of the academic product.